Sleep deprivation alters utilization of negative feedback in risky decision-making - Xu, Wenhao; Wang, Lubin; Yang, Liu; Zhu, Yuyang (Frontiers in Psychiatry, 2024)
BackgroundSleep loss has sometimes catastrophic effects on risky decision-making. However, it is unknown to what extent such deficits are exacerbated with increasing duration of sleep deprivation (SD) and whether sustained vigilant attention mediates this sleep deprivation-induced deficit.MethodsThe present study aimed to investigate the effect of 36 hours of SD on 37 male college students’ arousal, emotion, vigilant attention, and risky decision-making, using the Psychomotor Vigilance Test, the Game of Dice Task, and scales assessing fatigue, sleep, and emotions. ResultsCompared to baseline, SD significantly increased sleepiness, fatigue, and negative emotions, decreased positive emotions and vigilant attention, and led to a shift toward risky decision-making, and these effects often appeared 15 or 20 hours after SD. Interestingly, participants’ ability to employ positive feedback was maintained, whereas their performance to utilize negative feedback was impaired even after 8 hours of sleep deprivation. Meanwhile, vigilant attention acted as a mediator between SD and risky decision-making (z = -1.97, 95% [-6.00, -0.30]).DiscussionThese results suggest that sleep-deprived individuals are unable to use negative feedback to optimize their judgments, which may account for their poor decision-making under risk.